Coma - Cook, Robin (New York A Signet Book, 1977)
A young doctor at a Boston hospital becomes suspicious when healthy young people undergoing routine operations are mysteriously slipping into irreversible comas.
Keywords: Massachusetts--Boston -- Coma--Patients